A Marketing Strategy Analysis of ATS Tour and Travel During Covid-19 Pandemic - Ongko, Brian; Satrya, I Dewa Gde (E-Journal of Tourism; Volume 8 Number 1 (March 2021)DO - 10.24922/eot.v8i1.68935, 2021)
The spread of the Covid 19 Virus originating from China has made the world finally declare that this virus has become a pandemic status. One of the industries that have had a bad impact on the spread of this virus is tourism. Tour and Travel service providers that is struggling to survive this pandemic is ATS Tour and Travel. The problem experienced by the ATS Tour and Travel company today is the adjustment of the marketing strategy that will be used in the era of the pandemic that is affecting the world today. With these problems, the research was conducted qualitatively by interviewing 10 informants who were deemed to be representative to answer the problems that occurred during the Covid 19 pandemic. The results showed that in the indicators of crisis stages, ATS Tour and Travel had taken steps in all stages crisis well. In the indicator of disaster management, ATS Tour and Travel have also made its best efforts to prevent the impact of the COVID-19 pandemic, this includes health protocols that have been implemented, warning systems by only opening tourism in the green zone, informative media about Covid and tourist attractions that are not can be visited, disaster management by working with local guides and porters for site security and coordination. In the marketing strategy, it can be seen that currently, the target market for ATS Tour and Travel is changing, which initially served tour packages for foreign countries, is now starting to increase the domestic market.